Purification and Properties of Carbonic Anhydrase from Bone Marrow - Tasgin, Esen; Nadaroglu, Hayrunnisa; Demir, Yasar; Demir, Nazan (Asian Journal of Chemistry, 2010)
In this work, the carbonic anhydrase was purified from bovine bone marrow and investigated its kinetic properties. Carbonic anhydrase was purified from bovine bone marrow using affinity chromatography by sepharose 4B-L-tyrosine sulphanilamide. During purification steps, the activity of enzyme was measured using p-nitrophenyl acetate at pH: 7.4. Optimum pH and optimum temperature values for bovine bone marrow carbonic anhydrase were determined and then KM and Vmax values for the same substrate were obtained by means of Linewearver-Burk graphics. The purification degree for bovine bone marrow was calculated. The Vmax and KM values at optimum pH and at 20 ºC for the substrate (p-nitrophenyl acetate) were 120.418 μmol/L min and 2.409 × 10-3 mM, respectively. The Ki and I50 values for sulfanilamide, KSCN, NaN3 and acetazolamide were determined in bovine bone marrow carbonic anhydrase.